Leaching of waste battery paste components. Part 1: Lead citrate synthesis from PbO and PbO2 - Sonmez, M.S.; Kumar, R.V. (Elsevier BV, 2009)
Abstract In this study, as part of developing a new process which can avoid smelting and electro-winning, citric acid based reagents in aqueous media were reacted with PbO and PbO2. These two oxides are important components in the spent lead-acid battery paste and together account for up to 50% of the paste by weight. PbSO4, the main component in a spent battery paste accounting for the remaining 50%, is dealt with in Part 2 in a separate paper. Reaction between PbO and C6H8O7·H2O or PbO2 with a mixture of C6H8O7·H2O and H2O2 yielded lead citrate, Pb(C6H6O7)·H2O, which was characterised by XRD, SEM and FT-IR analysis. Optimal synthesis conditions were determined by investigating the effect of time, temperature, concentration, and the starting Pb oxide/water ratio. The optimal condition for leaching a mol of PbO at room temperature (20 °C) was found to be: 1 mol of (C6H8O7)·H2O solution; 1/3 as the starting PbO/water ratio and 15 min of reaction time. Pure citrate product, Pb(C6H6O7)·H2O was rapidly crystallized from the solution, in the leaching process. Leaching of PbO2 required the use of a mild reducing agent. For each mole of PbO2, the optimum condition at 20 °C was found to be: a solution containing 4 mol of C6H8O7·H2O and 2 mol of H2O2; 1/5 as the starting solid PbO2/water ratio; and 60 min of reaction time. The product, as with PbO, was pure Pb(C6H6O7)·H2O compound. The remaining lead content of the filtrate solution was 0.017% and 1% corresponding to recoveries of 99.98% and 99% of lead as citrate, after the leaching/crystallization/filtration process with PbO and PbO2, respectively. Asymmetric stretching vibrations between 1599 and 1662 cm− 1, whereas symmetric vibrations between 1520 and 1327 cm− 1 for lead citrate synthesised from PbO and asymmetric stretching vibrations between 1600 and 1642 cm− 1 as well as symmetric vibrations between 1517 and 1326 cm− 1 for the product obtained from PbO2 revealed the strong IR adsorptions associated with a carboxylate structure. XRD data was identical to the well documented crystalline Pb(C6H6O7)·H2O compound from both the oxides. SEM revealed the formation of plate/sheet like morphologies. The difference in the column size of the Pb(C6H6O7)·H2O formed from the two lead oxides can be related to difference in the rate of the respective reactions.